A hydrogen-sensitive color-changing tape containing platinum group oxides and a preparation method thereof
By using the Platinist PTO PTO catalyst and nano WO3/oxide graphene composite material in hydrogen -sensitive tape, combined with phosphate and amino -based modification, solve the problem of poor catalytic effects and poor adhesive performance in existing technologies. , Achieve more efficient hydrogen detection and good adhesion.
Patent Information
- Application Number
- CN202410609404.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-16
AI Technical Summary
The catalytic effect of precious metal catalysts in existing hydrogen-sensitive discoloration tapes is poor, and the tape adhesive performance is poor, resulting in the inability to effectively detect hydrogen leakage.
The Platinum oxide PTO is used as a catalyst. The composite material of nano -WO3 and graphene is combined with phosphate and amino -based modified treatment to improve the adhesive performance and catalytic activity of the tape.
It improves the catalytic performance of hydrogen -sensitive materials and the adhesion performance of the tape, realizes faster and sensitive hydrogen detection, and the adhesion performance of the tape at different temperatures is good.
Smart Images

Figure CN118325508B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of color-changing materials, and in particular relates to a hydrogen-sensitive color-changing tape containing platinum group oxides and a preparation method thereof. Background Art
[0002] Hydrogen is a reducing gas commonly used in modern industrial production and an important raw material for future clean energy. However, if hydrogen leaks during storage, transportation, and use, when the volume concentration of hydrogen in the air reaches 4%-75.6% (hydrogen explosion limit), it will explode when it encounters an open flame. Therefore, the detection of hydrogen content in the air is particularly important. Currently, the commonly used hydrogen leak detection method includes pressure monitoring, but local hydrogen leakage does not significantly change the system pressure, the detection effect is poor, and it is not easy to locate the hydrogen leakage point. With the development of technology, hydrogen sensitive materials are gradually being applied to the field of hydrogen detection.
[0003] Chinese patent application CN115505347A discloses a color-changing tape for hydrogen leak detection, including a bonding material and color-changing particles, wherein the bonding material is a silicon-based bonding material, and the color-changing particles are mesoporous multi-shell core particles, and the color-changing particle shell includes a mesoporous silica shell, a metal oxide-metal nanoparticle composite layer, and a silica particle core, wherein the silica particle core is a silicon dioxide core, the metal oxide is tungsten oxide, and the metal nanoparticles are nanopalladium particles. Tungsten oxide is a recoverable color-changing active material. During use, tungsten oxide and nanopalladium particles form a composite layer that changes color quickly after contacting hydrogen, and the color change speed is very fast. During the color change process, the nanopalladium particles play a catalytic role by capturing electrons and providing reactive sites. However, the nanopalladium particles in the single state have poor dispersion, few reactive sites, and the catalytic ability needs to be improved.
[0004] In addition, when the hydrogen-sensitive color-changing tape is used in hydrogen storage or transportation equipment, the adhesive properties of the hydrogen-sensitive color-changing tape may be weakened due to environmental factors, causing it to loosen or fall off, resulting in the inability to effectively detect hydrogen leaks. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides to solve the problems of poor catalytic effect of the precious metal catalyst contained in the hydrogen-sensitive color-changing tape in the prior art and poor adhesive performance of the tape.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides comprises the following steps:
[0008] Step 1: Mix sodium tungstate dihydrate with hydrochloric acid solution and acetic acid, and dissolve them to obtain a tungsten precursor solution;
[0009] After the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer is mixed and dissolved with ethanol, the tungsten precursor solution is added dropwise under stirring. After the addition is completed, stirring is continued until a sol is formed, and the solution is allowed to stand, dried, and calcined to obtain nano-WO3.
[0010] Nano-WO3 and graphene oxide (GO) are added to ethanol, and after ultrasonic dispersion, tetraammine platinum nitrate is added, mixed evenly, heated, and after heating, calcined to obtain GO / PtO / WO3 nano-composite material;
[0011] Step 2, adding γ-aminopropyltriethoxysilane to an ethanol aqueous solution, mixing evenly, adding GO / PtO / WO3 nanocomposite material, reacting, filtering, washing, and drying after the reaction is completed to obtain an amino-modified GO / PtO / WO3 nanocomposite material;
[0012] Step 3, dissolving epichlorohydrin in acetone to obtain an epichlorohydrin solution, and adding the epichlorohydrin solution dropwise to phosphoric acid. After the dropwise addition is completed, adding p-methoxyphenol, heating to a set temperature, reacting at the set temperature, and after the reaction is completed, distilling under reduced pressure to obtain chlorinated phosphate;
[0013] The amino-modified GO / PtO / WO3 nanocomposite and chlorinated phosphate are dispersed in acetone, aluminum chloride is added, and the reaction is carried out. After the reaction is completed, the mixture is filtered, washed, and dried to obtain a GO / PtO / WO3 nanocomposite grafted with phosphate;
[0014] Step 4: adding butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, and mixing well to obtain a mixed monomer solution;
[0015] adding dicumyl peroxide to ethyl acetate to obtain an initiator solution;
[0016] A portion of the mixed monomer solution is mixed with a portion of the initiator solution to react, and after the reaction is completed, the remaining mixed monomer solution and the remaining initiator solution are added dropwise, and after the addition is completed, the reaction is continued, and after the reaction is completed, a glue solution is obtained;
[0017] Adding GO / PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate into the adhesive solution, shearing and mixing, and degassing to obtain an adhesive;
[0018] Step 5: Apply adhesive on the base film, heat and cure, roll up, and mature to obtain a hydrogen-sensitive color-changing tape containing platinum group oxides.
[0019] Preferably, in the step 1, the mass ratio of sodium tungstate dihydrate, hydrochloric acid aqueous solution and acetic acid is 68:(15-20):(45-50);
[0020] The hydrochloric acid aqueous solution is a 37 wt % hydrochloric acid aqueous solution.
[0021] Preferably, in the step 1, the mass ratio of the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer, ethanol, and tungsten precursor solution is 6: (450-500): (128-138); the dripping time is 1-2h; the stirring speed is 800r / min; the standing condition is standing for 10-15h in an environment with a relative humidity of 50-70% and a temperature of 35-45°C; the drying condition is drying at a temperature of 60-70°C for 10-15h; and the calcination condition is calcining at a temperature of 500-600°C for 3.5-4.5h.
[0022] Preferably, in the step 1, the mass ratio of nano-WO3, graphene oxide, ethanol and tetraammine platinum nitrate is 1:(0.05-0.08):(60-90):(0.0018-0.0072); the ultrasonic dispersion conditions are: ultrasonic dispersion at a frequency of 20-40KHz for 10-20min, heating conditions are heating at a temperature of 100-120°C for 10-15h; and calcination conditions are calcination at a temperature of 350-450°C for 2.5-3.5h.
[0023] Preferably, in the step 2, the mass ratio of γ-aminopropyltriethoxysilane, ethanol aqueous solution, and GO / PtO / WO3 nanocomposite material is (25-30):(300-500):(22-24);
[0024] The ethanol aqueous solution is a 95wt% ethanol aqueous solution.
[0025] Preferably, in step 2, the reaction conditions are 60-80° C. for 2-3 hours.
[0026] Preferably, in step 3, the mass ratio of phosphoric acid, epichlorohydrin, acetone and p-methoxyphenol is 9.8:27.8:(75-100):(0.3-0.4); the set temperature is 75-85°C, and the reaction time is 8-12h.
[0027] Furthermore, the dripping time of the epichlorohydrin solution is 30-60 minutes.
[0028] Preferably, in step 3, the mass ratio of amino-modified GO / PtO / WO3 nanocomposite material, chlorinated phosphate, acetone and aluminum chloride is (35-40):(25-35):(200-300):(9-12), and the reaction conditions are reaction at a temperature of 40-50°C.
[0029] Further, when no HCl gas is produced during the reaction as measured by pH test paper, the reaction is complete.
[0030] Preferably, in step 4, the mass ratio of the mixed monomer solution to the initiator solution is (100-200):(12-18);
[0031] The part of the mixed monomer solution accounts for 1 / 5-1 / 3 of the mass of the mixed monomer solution, and the part of the initiator solution accounts for 1 / 5-1 / 3 of the mass of the initiator solution.
[0032] The reaction conditions are 75-85°C for 30-60 minutes; the temperature for continuing the reaction is 75-85°C, and when the viscosity of the reaction system reaches 2200-2500cp, the reaction is terminated.
[0033] Preferably, in the step 4, in the mixed monomer solution, the mass ratio of butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is (15-25):(45-55):(5-10):(5-10):(5-10):(2-5):(70-80);
[0034] In the initiator solution, the mass ratio of dicumyl peroxide to ethyl acetate is (0.5-1.5):(10-20).
[0035] Furthermore, the remaining mixed monomer solution and the remaining initiator solution are added dropwise for the same time period, which is 1-2 hours.
[0036] Preferably, in step 4, the mass ratio of the glue, GO / PtO / WO3 nanocomposite grafted phosphate, and isophorone diisocyanate is (155-220):(5-10):(0.5-3).
[0037] Preferably, in step five, the coating thickness is 0.03-0.05 mm; the heating and curing conditions are heating at 85-130° C. for 3-10 min; and the aging conditions are aging at 40-60° C. for 24-72 h.
[0038] Furthermore, the base film includes a PET (polyethylene terephthalate) film.
[0039] Preferably, a hydrogen-sensitive color-changing tape containing platinum group oxides is prepared by the above-mentioned method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The hydrogen-sensitive color-changing tape of the present invention uses nano WO3 as a hydrogen-sensitive color-changing material. After the nano WO3 contacts hydrogen, it can change from colorless to blue. The color-changing process can occur rapidly at room temperature and has high sensitivity. Compared with the use of a single substance of metal Pt as a catalyst, the platinum oxide PtO is used as a catalyst. Since the single substance of metal Pt will have a relatively serious particle aggregation phenomenon, the oxide PtO particles are more dispersed and have more active sites participating in the reaction, so that the hydrogen-sensitive performance of the nano WO3 is more excellent.
[0042] The adhesive prepared by polymerizing acrylic ester monomers in the present invention has the characteristics of high strength and high temperature resistance. Phosphate ester is added to the adhesive, and through the phosphating effect of the phosphate ester and the surface of the storage or transportation equipment material of hydrogen, a firm connection can be formed with the surface of the equipment material, and the bonding performance is good.
[0043] Graphene oxide has a good reinforcing effect due to the rich active groups such as hydroxyl and carboxyl on its surface. The addition of graphene oxide can improve the strength of the adhesive. Graphene oxide is loaded on nano-WO3, and the hydroxyl groups on the surface of nano-WO3 react with γ-aminopropyltriethoxysilane to introduce amino groups on the surface of GO / PtO / WO3 nanocomposite materials. The amino groups then react with chlorinated phosphate to obtain GO / PtO / WO3 nanocomposite materials grafted with phosphate. The phosphate is entangled with the polymerized acrylate molecules through the branched structure, which not only improves the dispersion performance of hydrogen-sensitive materials in the adhesive, but also improves the bonding performance of the adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The figure is a process flow chart of preparing GO / PtO / WO3 nanocomposite grafted phosphate in the present invention;
[0045] Figure 2 It is a line graph of the color change performance test results of the hydrogen-sensitive color-changing tapes prepared in Examples 1-5 and Comparative Examples 1-2 of the present invention;
[0046] Figure 3 It is a line graph of the adhesive performance test results of the hydrogen-sensitive color-changing tapes prepared in Examples 1-5 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION
[0047] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0048] Example 1
[0049] A method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides comprises the following steps:
[0050] Step 1: Mix sodium tungstate dihydrate, 37 wt % hydrochloric acid aqueous solution and acetic acid in a mass ratio of 68:15:45, and dissolve to obtain a tungsten precursor solution;
[0051] After the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68 and ethanol are mixed and dissolved, a tungsten precursor solution is added dropwise at a stirring speed of 800 r / min, the mass ratio of the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68, ethanol, and the tungsten precursor solution is 6:450:128, and the tungsten precursor solution is added dropwise for 1 hour. After the addition is completed, stirring is continued at a stirring speed of 800 r / min until a sol is formed, and the solution is allowed to stand for 15 hours in an environment with a relative humidity of 50% and a temperature of 35°C, dried at 60°C for 15 hours, and calcined at 500°C for 4.5 hours to obtain nano WO3;
[0052] Nano-WO3 and graphene oxide were added to ethanol, ultrasonically dispersed at a frequency of 20 KHz for 20 min, and tetraammine platinum nitrate was added. The mass ratio of nano-WO3, graphene oxide, ethanol, and tetraammine platinum nitrate was 1:0.05:60:0.0018. After mixing evenly, the mixture was heated at 100°C for 15 h. After heating, the mixture was calcined at 350°C for 3.5 h to obtain a GO / PtO / WO3 nanocomposite material.
[0053] Step 2: Add γ-aminopropyltriethoxysilane to 95wt% ethanol aqueous solution, mix well, and then add GO / PtO / WO3 nanocomposite material, the mass ratio of γ-aminopropyltriethoxysilane, 95wt% ethanol aqueous solution, and GO / PtO / WO3 nanocomposite material is 25:300:22, react at 60°C for 3h, filter after the reaction, wash with ethanol, and dry at 60°C for 15h to obtain amino-modified GO / PtO / WO3 nanocomposite material;
[0054] Step 3, dissolving epichlorohydrin in acetone to obtain an epichlorohydrin solution, and adding the epichlorohydrin solution dropwise to phosphoric acid. The dropping time of the epichlorohydrin solution is 30 minutes. After the dropping is completed, p-methoxyphenol is added. The mass ratio of phosphoric acid, epichlorohydrin, acetone, and p-methoxyphenol is 9.8:27.8:75:0.3. The temperature is raised to 75° C., and the reaction is carried out at 75° C. for 12 hours. After the reaction is completed, the reaction is carried out at 50° C. and under a vacuum degree of 0.05-0.08 MPa to obtain chlorinated phosphate;
[0055] The amino-modified GO / PtO / WO3 nanocomposite and chlorinated phosphate were dispersed in acetone, and aluminum chloride was added. The mass ratio of the amino-modified GO / PtO / WO3 nanocomposite, chlorinated phosphate, acetone, and aluminum chloride was 35:25:200:9. The reaction was carried out at 40°C. When the pH test paper was used to measure that no HCl gas was produced in the reaction, the reaction was completed. The mixture was filtered, washed with ethanol, and dried at 60°C for 15h to obtain GO / PtO / WO3 nanocomposite grafted phosphate.
[0056] Step 4: adding butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, and mixing well to obtain a mixed monomer solution;
[0057] In the mixed monomer solution, the mass ratio of butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 15:45:5:5:5:2:70;
[0058] adding dicumyl peroxide to ethyl acetate to obtain an initiator solution;
[0059] In the initiator solution, the mass ratio of dicumyl peroxide to ethyl acetate is 0.5:10;
[0060] The mass ratio of the mixed monomer solution to the initiator solution is 100:12;
[0061] A mixed monomer solution accounting for 1 / 5 of the mass of the mixed monomer solution and an initiator solution accounting for 1 / 5 of the mass of the initiator solution are mixed, and the reaction condition is to react at a temperature of 75°C for 60 minutes. After the reaction is completed, the remaining mixed monomer solution and the remaining initiator solution are added dropwise. The dropping time of the remaining mixed monomer solution and the remaining initiator solution is the same, both for 1 hour. After the dropping is completed, the reaction is continued at 75°C. When the viscosity of the reaction system is measured to reach 2200cp, the reaction is terminated to obtain a glue solution;
[0062] Adding GO / PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate into the glue solution, wherein the mass ratio of the glue solution, the GO / PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate is 155:5:0.5, shear mixing, vacuum degassing, and obtaining an adhesive;
[0063] Step 5: Apply adhesive on the PET film, the thickness of the PET film is 0.1 mm, the thickness of the adhesive is 0.05 mm, heat at 85°C for 10 min, roll up, and age at 40°C for 72 h to obtain a hydrogen-sensitive color-changing tape containing platinum group oxides.
[0064] Example 2
[0065] A method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides comprises the following steps:
[0066] Step 1: Sodium tungstate dihydrate, 37 wt % hydrochloric acid aqueous solution and acetic acid are mixed and dissolved in a mass ratio of 68:20:50 to obtain a tungsten precursor solution;
[0067] After the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68 and ethanol are mixed and dissolved, a tungsten precursor solution is added dropwise at a stirring speed of 800 r / min, the mass ratio of the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68, ethanol, and the tungsten precursor solution is 6:500:138, and the tungsten precursor solution is added dropwise for 2 hours. After the addition is completed, stirring is continued at a stirring speed of 800 r / min until a sol is formed, and the sol is allowed to stand for 10 hours in an environment with a relative humidity of 70% and a temperature of 45°C, dried at 60°C for 15 hours, and calcined at 600°C for 3.5 hours to obtain nano WO3;
[0068] Nano-WO3 and graphene oxide were added to ethanol, ultrasonically dispersed at a frequency of 40KHz for 10 minutes, and tetraammine platinum nitrate was added. The mass ratio of nano-WO3, graphene oxide, ethanol, and tetraammine platinum nitrate was 1:0.08:90:0.0072. After mixing evenly, the mixture was heated at 120°C for 10 hours. After heating, the mixture was calcined at 450°C for 2.5 hours to obtain a GO / PtO / WO3 nanocomposite material.
[0069] Step 2: Add γ-aminopropyltriethoxysilane to 95wt% ethanol aqueous solution, mix well, and then add GO / PtO / WO3 nanocomposite material, the mass ratio of γ-aminopropyltriethoxysilane, 95wt% ethanol aqueous solution, and GO / PtO / WO3 nanocomposite material is 30:500:24, react at 80°C for 2h, filter after the reaction, wash with ethanol, and dry at 60°C for 15h to obtain amino-modified GO / PtO / WO3 nanocomposite material;
[0070] Step 3, dissolving epichlorohydrin in acetone to obtain an epichlorohydrin solution, and adding the epichlorohydrin solution dropwise to phosphoric acid, wherein the dropping time of the epichlorohydrin solution is 60 min. After the dropping is completed, p-methoxyphenol is added, and the mass ratio of phosphoric acid, epichlorohydrin, acetone, and p-methoxyphenol is 9.8:27.8:100:0.4. The temperature is raised to 85° C., and the reaction is carried out at 85° C. for 8 hours. After the reaction is completed, the reaction is carried out under reduced pressure distillation at 50° C. and a vacuum degree of 0.05-0.08 MPa to obtain chlorinated phosphate;
[0071] The amino-modified GO / PtO / WO3 nanocomposite and chlorinated phosphate were dispersed in acetone, and aluminum chloride was added. The mass ratio of the amino-modified GO / PtO / WO3 nanocomposite, chlorinated phosphate, acetone, and aluminum chloride was 40:35:300:12. The reaction was carried out at 50°C. When the pH test paper was used to measure that no HCl gas was produced in the reaction, the reaction was completed. The mixture was filtered, washed with ethanol, and dried at 60°C for 15h to obtain GO / PtO / WO3 nanocomposite grafted phosphate.
[0072] Step 4: adding butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, and mixing well to obtain a mixed monomer solution;
[0073] In the mixed monomer solution, the mass ratio of butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 25:55:10:10:10:5:80;
[0074] adding dicumyl peroxide to ethyl acetate to obtain an initiator solution;
[0075] In the initiator solution, the mass ratio of dicumyl peroxide to ethyl acetate is 1.5:20;
[0076] The mass ratio of the mixed monomer solution to the initiator solution is 200:18;
[0077] A mixed monomer solution accounting for 1 / 3 of the mass of the mixed monomer solution and an initiator solution accounting for 1 / 3 of the mass of the initiator solution are mixed, and the reaction condition is to react at a temperature of 85°C for 30 minutes. After the reaction is completed, the remaining mixed monomer solution and the remaining initiator solution are added dropwise. The dropping time of the remaining mixed monomer solution and the remaining initiator solution is the same, both for 2 hours. After the dropping is completed, the reaction is continued at a temperature of 85°C. When the viscosity of the reaction system is measured to reach 2500cp, the reaction is terminated to obtain a glue solution;
[0078] Adding GO / PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate into the glue solution, wherein the mass ratio of the glue solution, the GO / PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate is 220:10:3, shear mixing, vacuum degassing, and obtaining an adhesive;
[0079] Step 5: Apply adhesive on the PET film, the thickness of the PET film is 0.1 mm, the thickness of the adhesive is 0.03 mm, heat at 130°C for 3 minutes, roll up, and age at 60°C for 24 hours to obtain a hydrogen-sensitive color-changing tape containing platinum group oxides.
[0080] Example 3
[0081] A method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides comprises the following steps:
[0082] Step 1: Sodium tungstate dihydrate, 37 wt % hydrochloric acid aqueous solution and acetic acid are mixed and dissolved in a mass ratio of 68:16:46 to obtain a tungsten precursor solution;
[0083] After the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68 and ethanol are mixed and dissolved, a tungsten precursor solution is added dropwise at a stirring speed of 800 r / min, the mass ratio of the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68, ethanol, and the tungsten precursor solution is 6:465:130, and the tungsten precursor solution is added dropwise for 1 hour. After the addition is completed, stirring is continued at a stirring speed of 800 r / min until a sol is formed, and the sol is allowed to stand for 14 hours in an environment with a relative humidity of 55% and a temperature of 35°C, dried at 60°C for 15 hours, and calcined at 550°C for 4 hours to obtain nano WO3;
[0084] Nano-WO3 and graphene oxide were added to ethanol, ultrasonically dispersed at a frequency of 30 KHz for 15 minutes, and tetraammine platinum nitrate was added. The mass ratio of nano-WO3, graphene oxide, ethanol, and tetraammine platinum nitrate was 1:0.06:70:0.0036. After mixing evenly, the mixture was heated at 105°C for 14 hours. After heating, the mixture was calcined at 400°C for 3 hours to obtain a GO / PtO / WO3 nanocomposite material.
[0085] Step 2: Add γ-aminopropyltriethoxysilane to 95wt% ethanol aqueous solution, mix well, and then add GO / PtO / WO3 nanocomposite material, the mass ratio of γ-aminopropyltriethoxysilane, 95wt% ethanol aqueous solution, and GO / PtO / WO3 nanocomposite material is 26.5:350:22.5, react at 70°C for 2.5h, filter after the reaction, wash with ethanol, and dry at 60°C for 15h to obtain amino-modified GO / PtO / WO3 nanocomposite material;
[0086] Step 3, dissolving epichlorohydrin in acetone to obtain an epichlorohydrin solution, and adding the epichlorohydrin solution dropwise to phosphoric acid, wherein the dropping time of the epichlorohydrin solution is 40 min. After the dropping is completed, p-methoxyphenol is added, and the mass ratio of phosphoric acid, epichlorohydrin, acetone, and p-methoxyphenol is 9.8:27.8:80:0.33. The temperature is raised to 80° C., and the reaction is carried out at 80° C. for 10 hours. After the reaction is completed, the reaction is carried out at 50° C. and under a vacuum degree of 0.05-0.08 MPa to obtain chlorinated phosphate;
[0087] The amino-modified GO / PtO / WO3 nanocomposite and chlorinated phosphate were dispersed in acetone, and aluminum chloride was added. The mass ratio of the amino-modified GO / PtO / WO3 nanocomposite, chlorinated phosphate, acetone, and aluminum chloride was 36:28:230:9.5. The reaction was carried out at 45°C. When the pH test paper was used to measure that no HCl gas was produced in the reaction, the reaction was completed. The mixture was filtered, washed with ethanol, and dried at 60°C for 15h to obtain GO / PtO / WO3 nanocomposite grafted phosphate.
[0088] Step 4: adding butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, and mixing well to obtain a mixed monomer solution;
[0089] In the mixed monomer solution, the mass ratio of butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 18:47:6:6.5:6:3:72;
[0090] adding dicumyl peroxide to ethyl acetate to obtain an initiator solution;
[0091] In the initiator solution, the mass ratio of dicumyl peroxide to ethyl acetate is 0.8:12.5;
[0092] The mass ratio of the mixed monomer solution to the initiator solution is 125:13.5;
[0093] A mixed monomer solution accounting for 1 / 4 of the mass of the mixed monomer solution and an initiator solution accounting for 1 / 4 of the mass of the initiator solution are mixed, and the reaction condition is to react at a temperature of 75°C for 55 minutes. After the reaction is completed, the remaining mixed monomer solution and the remaining initiator solution are added dropwise. The dropping time of the remaining mixed monomer solution and the remaining initiator solution is the same, both for 1.5 hours. After the dropping is completed, the reaction is continued at 75°C. When the viscosity of the reaction system is measured to reach 2300cp, the reaction is terminated to obtain a glue solution;
[0094] Adding GO / PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate into the glue solution, wherein the mass ratio of the glue solution, the GO / PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate is 170:6:1.2, shear mixing, vacuum degassing, and obtaining an adhesive;
[0095] Step 5: Apply adhesive on the PET film, the thickness of the PET film is 0.1 mm, the thickness of the adhesive is 0.045 mm, heat at 95°C for 8 minutes, roll up, and age at 45°C for 60 hours to obtain a hydrogen-sensitive color-changing tape containing platinum group oxides.
[0096] Example 4
[0097] A method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides comprises the following steps:
[0098] Step 1: Sodium tungstate dihydrate, 37 wt % hydrochloric acid aqueous solution and acetic acid are mixed and dissolved in a mass ratio of 68:17.5:47.5 to obtain a tungsten precursor solution;
[0099] After the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68 and ethanol are mixed and dissolved, a tungsten precursor solution is added dropwise at a stirring speed of 800 r / min, the mass ratio of the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68, ethanol, and the tungsten precursor solution is 6:475:133, and the tungsten precursor solution is added dropwise for 1.5 hours. After the addition is completed, stirring is continued at a stirring speed of 800 r / min until a sol is formed, and the sol is allowed to stand for 13 hours in an environment with a relative humidity of 60% and a temperature of 40°C, dried at 60°C for 15 hours, and calcined at 550°C for 4 hours to obtain nano WO3;
[0100] Nano-WO3 and graphene oxide were added to ethanol, ultrasonically dispersed at a frequency of 40KHz for 10 minutes, and tetraammine platinum nitrate was added. The mass ratio of nano-WO3, graphene oxide, ethanol, and tetraammine platinum nitrate was 1:0.65:75:0.0045. After mixing evenly, the mixture was heated at 110°C for 13 hours. After heating, the mixture was calcined at 400°C for 3 hours to obtain a GO / PtO / WO3 nanocomposite material.
[0101] Step 2: Add γ-aminopropyltriethoxysilane to 95wt% ethanol aqueous solution, mix well, and then add GO / PtO / WO3 nanocomposite material, the mass ratio of γ-aminopropyltriethoxysilane, 95wt% ethanol aqueous solution, and GO / PtO / WO3 nanocomposite material is 27.5:400:23, react at 70°C for 2.5h, filter after the reaction, wash with ethanol, and dry at 60°C for 15h to obtain amino-modified GO / PtO / WO3 nanocomposite material;
[0102] Step 3, dissolving epichlorohydrin in acetone to obtain an epichlorohydrin solution, and adding the epichlorohydrin solution dropwise to phosphoric acid. The dropping time of the epichlorohydrin solution is 45 minutes. After the dropping is completed, p-methoxyphenol is added. The mass ratio of phosphoric acid, epichlorohydrin, acetone, and p-methoxyphenol is 9.8:27.8:85:0.35. The temperature is raised to 80° C., and the reaction is carried out at 80° C. for 10 hours. After the reaction is completed, the temperature is 50° C. and the vacuum degree is 0.05-0.08 MPa to obtain chlorinated phosphate;
[0103] The amino-modified GO / PtO / WO3 nanocomposite and chlorinated phosphate were dispersed in acetone, and aluminum chloride was added. The mass ratio of the amino-modified GO / PtO / WO3 nanocomposite, chlorinated phosphate, acetone, and aluminum chloride was 37.5:30:255:10. The reaction was carried out at 45°C. When the pH test paper was used to measure that no HCl gas was produced in the reaction, the reaction was completed. The mixture was filtered, washed with ethanol, and dried at 60°C for 15h to obtain GO / PtO / WO3 nanocomposite grafted phosphate.
[0104] Step 4: adding butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, and mixing well to obtain a mixed monomer solution;
[0105] In the mixed monomer solution, the mass ratio of butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 20:50:7.5:7.5:7:3.5:75;
[0106] adding dicumyl peroxide to ethyl acetate to obtain an initiator solution;
[0107] In the initiator solution, the mass ratio of dicumyl peroxide to ethyl acetate is 1:15.5;
[0108] The mass ratio of the mixed monomer solution to the initiator solution is 150:15;
[0109] A mixed monomer solution accounting for 1 / 4 of the mass of the mixed monomer solution and an initiator solution accounting for 1 / 4 of the mass of the initiator solution are mixed, and the reaction condition is to react at 80°C for 45 minutes. After the reaction is completed, the remaining mixed monomer solution and the remaining initiator solution are added dropwise. The dropping time of the remaining mixed monomer solution and the remaining initiator solution is the same, both for 1.5 hours. After the dropwise addition is completed, the reaction is continued at 80°C. When the viscosity of the reaction system is measured to reach 2350cp, the reaction is terminated to obtain a glue solution;
[0110] Adding GO / PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate into the glue solution, wherein the mass ratio of the glue solution, the GO / PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate is 185:7:1.8, shear mixing, vacuum degassing, and obtaining an adhesive;
[0111] Step 5: Use adhesive to coat the PET film, the thickness of the PET film is 0.1 mm, the coating thickness is 0.04 mm, heat at 105°C for 6.5 min, roll up, and age at 50°C for 48 h to obtain a hydrogen-sensitive color-changing tape containing platinum group oxides.
[0112] Example 5
[0113] A method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides comprises the following steps:
[0114] Step 1: Sodium tungstate dihydrate, 37 wt % hydrochloric acid aqueous solution and acetic acid are mixed and dissolved in a mass ratio of 68:18.5:49 to obtain a tungsten precursor solution;
[0115] After the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68 and ethanol are mixed and dissolved, a tungsten precursor solution is added dropwise at a stirring speed of 800 r / min, the mass ratio of the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68, ethanol, and the tungsten precursor solution is 6:485:136, and the tungsten precursor solution is added dropwise for 2 hours. After the addition is completed, stirring is continued at a stirring speed of 800 r / min until a sol is formed, and the solution is allowed to stand for 12 hours in an environment with a relative humidity of 65% and a temperature of 45°C, dried at a temperature of 60°C for 15 hours, and calcined at a temperature of 550°C for 4 hours to obtain nano WO3;
[0116] Nano-WO3 and graphene oxide were added to ethanol, ultrasonically dispersed at a frequency of 40KHz for 10 minutes, and tetraammine platinum nitrate was added. The mass ratio of nano-WO3, graphene oxide, ethanol, and tetraammine platinum nitrate was 1:0.07:80:0.0054. After mixing evenly, the mixture was heated at 115°C for 12 hours. After heating, the mixture was calcined at 400°C for 3 hours to obtain a GO / PtO / WO3 nanocomposite material.
[0117] Step 2: Add γ-aminopropyltriethoxysilane to 95wt% ethanol aqueous solution, mix well, and then add GO / PtO / WO3 nanocomposite material, the mass ratio of γ-aminopropyltriethoxysilane, 95wt% ethanol aqueous solution, and GO / PtO / WO3 nanocomposite material is 28.5:450:23.5, react at 70°C for 2.5h, filter after the reaction, wash with ethanol, and dry at 60°C for 15h to obtain amino-modified GO / PtO / WO3 nanocomposite material;
[0118] Step 3, dissolving epichlorohydrin in acetone to obtain an epichlorohydrin solution, and adding the epichlorohydrin solution dropwise to phosphoric acid, wherein the dropping time of the epichlorohydrin solution is 50 min. After the dropping is completed, p-methoxyphenol is added, and the mass ratio of phosphoric acid, epichlorohydrin, acetone, and p-methoxyphenol is 9.8:27.8:90:0.38. The temperature is raised to 80° C., and the reaction is carried out at 80° C. for 10 hours. After the reaction is completed, the reaction is carried out at 50° C. and under a vacuum degree of 0.05-0.08 MPa to obtain chlorinated phosphate;
[0119] The amino-modified GO / PtO / WO3 nanocomposite and chlorinated phosphate were dispersed in acetone, and aluminum chloride was added. The mass ratio of the amino-modified GO / PtO / WO3 nanocomposite, chlorinated phosphate, acetone, and aluminum chloride was 39:33:280:11. The reaction was carried out at 45°C. When the pH test paper was used to measure that no HCl gas was produced in the reaction, the reaction was completed. The mixture was filtered, washed with ethanol, and dried at 60°C for 15h to obtain GO / PtO / WO3 nanocomposite grafted phosphate.
[0120] Step 4: adding butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, and mixing well to obtain a mixed monomer solution;
[0121] In the mixed monomer solution, the mass ratio of butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 23:52:9:9:8:4:78;
[0122] adding dicumyl peroxide to ethyl acetate to obtain an initiator solution;
[0123] In the initiator solution, the mass ratio of dicumyl peroxide to ethyl acetate is 1.2:18;
[0124] The mass ratio of the mixed monomer solution to the initiator solution is 175:16.5;
[0125] A mixed monomer solution accounting for 1 / 4 of the mass of the mixed monomer solution and an initiator solution accounting for 1 / 4 of the mass of the initiator solution are mixed, and the reaction condition is to react at 85°C for 35 minutes. After the reaction is completed, the remaining mixed monomer solution and the remaining initiator solution are added dropwise. The dropping time of the remaining mixed monomer solution and the remaining initiator solution is the same, both for 1.5 hours. After the dropwise addition is completed, the reaction is continued at 85°C. When the viscosity of the reaction system is measured to reach 2400cp, the reaction is terminated to obtain a glue solution;
[0126] Adding GO / PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate into the glue solution, wherein the mass ratio of the glue solution, GO / PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate is 205:8:2.4, shear mixing, vacuum degassing, and obtaining an adhesive;
[0127] Step 5: Use adhesive to coat the PET film, the thickness of the PET film is 0.1 mm, the coating thickness is 0.035 mm, heat at 120°C for 5 minutes, roll up, and age at 55°C for 36 hours to obtain a hydrogen-sensitive color-changing tape containing platinum group oxides.
[0128] Comparative Example 1
[0129] A method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides comprises the following steps:
[0130] Step 1: Mix sodium tungstate dihydrate, 37 wt % hydrochloric acid aqueous solution and acetic acid in a mass ratio of 68:15:45, and dissolve to obtain a tungsten precursor solution;
[0131] After the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68 and ethanol are mixed and dissolved, a tungsten precursor solution is added dropwise at a stirring speed of 800 r / min, the mass ratio of the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68, ethanol, and the tungsten precursor solution is 6:450:128, and the tungsten precursor solution is added dropwise for 1 hour. After the addition is completed, stirring is continued at a stirring speed of 800 r / min until a sol is formed, and the solution is allowed to stand for 15 hours in an environment with a relative humidity of 50% and a temperature of 35°C, dried at 60°C for 15 hours, and calcined at 500°C for 4.5 hours to obtain nano WO3;
[0132] The nano-WO3 was added to ethanol, ultrasonically dispersed at a frequency of 20 KHz for 20 minutes, and tetraammine platinum nitrate was added. The mass ratio of nano-WO3, ethanol and tetraammine platinum nitrate was 1:60:0.0018. After being evenly mixed, the mixture was heated at 100°C for 15 hours. After the heating was completed, the mixture was calcined at 350°C for 3.5 hours to obtain a PtO / WO3 nano-composite material.
[0133] Step 2: Add γ-aminopropyltriethoxysilane to 95wt% ethanol aqueous solution, mix well, add PtO / WO3 nanocomposite material, the mass ratio of γ-aminopropyltriethoxysilane, 95wt% ethanol aqueous solution, and PtO / WO3 nanocomposite material is 25:300:22, react at 60°C for 3h, filter after the reaction, wash with ethanol, and dry at 60°C for 15h to obtain amino-modified PtO / WO3 nanocomposite material;
[0134] Step 3, dissolving epichlorohydrin in acetone to obtain an epichlorohydrin solution, and adding the epichlorohydrin solution dropwise to phosphoric acid. The dropping time of the epichlorohydrin solution is 30 minutes. After the dropping is completed, p-methoxyphenol is added. The mass ratio of phosphoric acid, epichlorohydrin, acetone, and p-methoxyphenol is 9.8:27.8:75:0.3. The temperature is raised to 75° C., and the reaction is carried out at 75° C. for 12 hours. After the reaction is completed, the reaction is carried out at 50° C. and under a vacuum degree of 0.05-0.08 MPa to obtain chlorinated phosphate;
[0135] The amino-modified PtO / WO3 nanocomposite material and chlorinated phosphate are dispersed in acetone, and aluminum chloride is added. The mass ratio of the amino-modified PtO / WO3 nanocomposite material, chlorinated phosphate, acetone, and aluminum chloride is 35:25:200:9. The reaction is carried out at 40°C. When the pH test paper is used to measure that no HCl gas is generated in the reaction, the reaction is completed. The mixture is filtered, washed with ethanol, and dried at 60°C for 15 hours to obtain a PtO / WO3 nanocomposite material grafted with phosphate.
[0136] Step 4: adding butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, and mixing well to obtain a mixed monomer solution;
[0137] In the mixed monomer solution, the mass ratio of butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 15:45:5:5:5:2:70;
[0138] adding dicumyl peroxide to ethyl acetate to obtain an initiator solution;
[0139] In the initiator solution, the mass ratio of dicumyl peroxide to ethyl acetate is 0.5:10;
[0140] The mass ratio of the mixed monomer solution to the initiator solution is 100:12;
[0141] A mixed monomer solution accounting for 1 / 5 of the mass of the mixed monomer solution and an initiator solution accounting for 1 / 5 of the mass of the initiator solution are mixed, and the reaction condition is to react at a temperature of 75°C for 60 minutes. After the reaction is completed, the remaining mixed monomer solution and the remaining initiator solution are added dropwise. The dropping time of the remaining mixed monomer solution and the remaining initiator solution is the same, both for 1 hour. After the dropping is completed, the reaction is continued at 75°C. When the viscosity of the reaction system is measured to reach 2200cp, the reaction is terminated to obtain a glue solution;
[0142] Adding PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate to the glue solution, wherein the mass ratio of the glue solution, the PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate is 155:5:0.5, shear mixing, vacuum degassing, and obtaining an adhesive;
[0143] Step 5: Apply adhesive on the PET film, the thickness of the PET film is 0.1 mm, the thickness of the adhesive is 0.05 mm, heat at 85°C for 10 min, roll up, and age at 40°C for 72 h to obtain a hydrogen-sensitive color-changing tape containing platinum group oxides.
[0144] Comparative Example 2
[0145] A method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides comprises the following steps:
[0146] Step 1: Mix sodium tungstate dihydrate, 37 wt % hydrochloric acid aqueous solution and acetic acid in a mass ratio of 68:15:45, and dissolve to obtain a tungsten precursor solution;
[0147] After the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68 and ethanol are mixed and dissolved, a tungsten precursor solution is added dropwise at a stirring speed of 800 r / min, the mass ratio of the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer Pluronic F68, ethanol, and the tungsten precursor solution is 6:450:128, and the tungsten precursor solution is added dropwise for 1 hour. After the addition is completed, stirring is continued at a stirring speed of 800 r / min until a sol is formed, and the solution is allowed to stand for 15 hours in an environment with a relative humidity of 50% and a temperature of 35°C, dried at 60°C for 15 hours, and calcined at 500°C for 4.5 hours to obtain nano WO3;
[0148] Nano-WO3 and graphene oxide were added to ethanol, ultrasonically dispersed at a frequency of 20 KHz for 20 min, and tetraammine platinum nitrate was added. The mass ratio of nano-WO3, graphene oxide, ethanol, and tetraammine platinum nitrate was 1:0.05:60:0.0018. After mixing evenly, the mixture was heated at 100°C for 15 h. After heating, the mixture was calcined at 350°C for 3.5 h to obtain a GO / PtO / WO3 nanocomposite material.
[0149] Step 4: adding butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, and mixing well to obtain a mixed monomer solution;
[0150] In the mixed monomer solution, the mass ratio of butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 15:45:5:5:5:2:70;
[0151] adding dicumyl peroxide to ethyl acetate to obtain an initiator solution;
[0152] In the initiator solution, the mass ratio of dicumyl peroxide to ethyl acetate is 0.5:10;
[0153] The mass ratio of the mixed monomer solution to the initiator solution is 100:12;
[0154] A mixed monomer solution accounting for 1 / 5 of the mass of the mixed monomer solution and an initiator solution accounting for 1 / 5 of the mass of the initiator solution are mixed, and the reaction condition is to react at a temperature of 75°C for 60 minutes. After the reaction is completed, the remaining mixed monomer solution and the remaining initiator solution are added dropwise. The dropping time of the remaining mixed monomer solution and the remaining initiator solution is the same, both for 1 hour. After the dropping is completed, the reaction is continued at 75°C. When the viscosity of the reaction system is measured to reach 2200cp, the reaction is terminated to obtain a glue solution;
[0155] Adding GO / PtO / WO3 nanocomposite and isophorone diisocyanate to the glue solution, wherein the mass ratio of the glue solution, the GO / PtO / WO3 nanocomposite and the isophorone diisocyanate is 155:5:0.5, shear mixing, vacuum degassing, and obtaining an adhesive;
[0156] Step 5: Apply adhesive on the PET film, the thickness of the PET film is 0.1 mm, the thickness of the adhesive is 0.05 mm, heat at 85°C for 10 min, roll up, and age at 40°C for 72 h to obtain a hydrogen-sensitive color-changing tape containing platinum group oxides.
[0157] Test example
[0158] The performance tests were performed on the hydrogen-sensitive color-changing tapes containing platinum group oxides prepared in Examples 1-5 and Comparative Examples 1-2:
[0159] (1) Color change performance test: The adhesive tapes prepared in Examples 1-5 and Comparative Examples 1-2 were wound around the outside of seven pre-prepared pipelines with the same leaking points, and the adhesive tapes were fixed by using their self-adhesiveness; a mixed gas consisting of 1% hydrogen and 99% nitrogen by volume was introduced into the pipelines at a rate of 1 L / min, and the color change of the adhesive tapes at the leaking points was observed, and the color change time was recorded;
[0160] The test results are shown in Table 1:
[0161] Table 1
[0162] Color change time(s) Color change time(s) Example 1 27 Example 5 25 Example 2 24 Comparative Example 1 27 Example 3 26 Comparative Example 2 28 Example 4 26
[0163] As shown in Table 1, the hydrogen-sensitive color-changing tape prepared by the present invention has high color-changing sensitivity and fast color-changing speed. Under the catalytic action of the platinum oxide PtO, the hydrogen-sensitive material nano WO3 reacts with hydrogen to change color. Compared with Example 1, in Comparative Example 1, graphene oxide is not added, which does not affect the color-changing performance of the hydrogen-sensitive color-changing tape, and the color-changing time is equivalent to that of Example 1.
[0164] (2) Adhesion performance test: The 180° peel strength of the adhesive tapes prepared in Examples 1-5 and Comparative Examples 1-2 at -55°C, 25°C and 150°C was measured respectively. The test method was based on the standard GB / 2792-2014 "Test method for peel strength of adhesive tapes". The test results are shown in Table 2:
[0165] Table 2
[0166]
[0167] As shown in Table 2, the hydrogen-sensitive color-changing tape prepared by the present invention has good bonding properties. The amino groups introduced on the surface of the GO / PtO / WO3 nanocomposite react with the chlorinated phosphate to obtain the GO / PtO / WO3 nanocomposite grafted phosphate. The phosphate and the surface of the hydrogen storage or transportation equipment material are phosphatized to form a firm connection with the surface of the equipment material, and the bonding performance is good. Compared with Example 1, in Comparative Example 1, since no graphene oxide is added, the hydroxyl groups on the surface of the GO / PtO / WO3 nanocomposite are reduced, the introduced phosphate is reduced, and the bonding performance is reduced; in Comparative Example 2, since phosphate is introduced on the surface of the GO / PtO / WO3 nanocomposite, the bonding performance is greatly reduced.
[0168] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is determined by the appended claims.
[0169] Claims and their equivalents.
Claims
1. A method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides, characterized in that: The following steps are involved: Step 1: Add nano-WO3 and graphene oxide to ethanol, disperse them by ultrasonication, add tetraammine platinum nitrate, mix them evenly, heat them, and after heating, calcine them to obtain GO / PtO / WO3 nano-composite materials; Step 2, adding γ-aminopropyltriethoxysilane to an ethanol aqueous solution, mixing evenly, adding GO / PtO / WO3 nanocomposite material, reacting, filtering, washing, and drying after the reaction is completed to obtain an amino-modified GO / PtO / WO3 nanocomposite material; Step 3, dissolving epichlorohydrin in acetone to obtain an epichlorohydrin solution, and adding the epichlorohydrin solution dropwise to phosphoric acid. After the dropwise addition is completed, adding p-methoxyphenol, heating to a set temperature, reacting at the set temperature, and after the reaction is completed, distilling under reduced pressure to obtain chlorinated phosphate; The amino-modified GO / PtO / WO3 nanocomposite and chlorinated phosphate are dispersed in acetone, aluminum chloride is added, and the reaction is carried out. After the reaction is completed, the mixture is filtered, washed, and dried to obtain a GO / PtO / WO3 nanocomposite grafted with phosphate; The mass ratio of amino-modified GO / PtO / WO3 nanocomposite material, chlorinated phosphate, acetone and aluminum chloride is (35-40):(25-35):(200-300):(9-12), and the reaction conditions are 40-50°C. Step 4: adding butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, and mixing them evenly to obtain a mixed monomer solution; adding diisopropylbenzene peroxide to ethyl acetate to obtain an initiator solution; A portion of the mixed monomer solution is mixed with a portion of the initiator solution to react, and after the reaction is completed, the remaining mixed monomer solution and the remaining initiator solution are added dropwise, and after the addition is completed, the reaction is continued, and after the reaction is completed, a glue solution is obtained; Adding GO / PtO / WO3 nanocomposite grafted phosphate and isophorone diisocyanate into the adhesive solution, shearing and mixing, and degassing to obtain an adhesive; Step 5: Apply adhesive on the base film, heat and cure, roll up, and age to obtain a hydrogen-sensitive color-changing tape containing platinum group oxides.
2. The method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides according to claim 1, characterized in that: The nano WO3 in step 1 is prepared by the following steps: Mixing sodium tungstate dihydrate with hydrochloric acid aqueous solution and acetic acid, dissolving, and obtaining a tungsten precursor solution; After the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer is mixed and dissolved with ethanol, the tungsten precursor solution is added dropwise under stirring. After the addition is completed, stirring is continued until a sol is formed, and the solution is allowed to stand, dried, and calcined to obtain nano WO3.
3. The method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides according to claim 2, characterized in that: The mass of sodium tungstate dihydrate, hydrochloric acid aqueous solution, and acetic acid is 68:(15-20):(45-50); The mass ratio of the nonionic surfactant polyoxyethylene polyoxypropylene ether block copolymer, ethanol, and tungsten precursor solution is 6:(450-500):(128-138); the calcination condition is calcination at a temperature of 500-600° C. for 3.5-4.5 hours.
4. The method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides according to claim 1, characterized in that: In the step 1, the mass ratio of nano-WO3, graphene oxide, ethanol, and tetraammine platinum nitrate is 1: (0.05-0.08): (60-90): (0.0018-0.0072); the ultrasonic dispersion conditions are: ultrasonic dispersion at a frequency of 20-40KHz for 10-20min, heating conditions are heating at a temperature of 100-120°C for 10-15h; and calcination conditions are calcination at a temperature of 350-450°C for 2.5-3.5h.
5. The method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides according to claim 1, characterized in that: In the step 2, the mass ratio of γ-aminopropyltriethoxysilane, ethanol aqueous solution, and GO / PtO / WO3 nanocomposite material is (25-30):(300-500):(22-24), and the reaction conditions are 60-80°C for 2-3h.
6. The method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides according to claim 1, characterized in that: In the step 3, the mass ratio of phosphoric acid, epichlorohydrin, acetone and p-methoxyphenol is 9.8:27.8:(75-100):(0.3-0.4); the set temperature is 75-85° C., and the reaction time is 8-12 h.
7. The method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides according to claim 1, characterized in that: In the step 4, the mass ratio of the mixed monomer solution to the initiator solution is (100-200):(12-18); The part of the mixed monomer solution accounts for 1 / 5-1 / 3 of the mass of the mixed monomer solution, and the part of the initiator solution accounts for 1 / 5-1 / 3 of the mass of the initiator solution. The reaction conditions are 75-85°C for 30-60 minutes; the temperature for continuing the reaction is 75-85°C, and when the viscosity of the reaction system reaches 2200-2500cp, the reaction is terminated; Wherein, in the mixed monomer solution, the mass ratio of butyl acrylate, lauryl methacrylate, tetrahydrofuran methacrylate, isobutyl methacrylate, glycidyl methacrylate, hydroxyethyl methacrylate and ethyl acetate is (15-25):(45-55):(5-10):(5-10):(5-10):(2-5):(70-80); In the initiator solution, the mass ratio of dicumyl peroxide to ethyl acetate is (0.5-1.5):(10-20).
8. The method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides according to claim 1, characterized in that: In the step 4, the mass ratio of the glue, the GO / PtO / WO3 nanocomposite grafted phosphate, and isophorone diisocyanate is (155-220):(5-10):(0.5-3).
9. A hydrogen-sensitive color-changing tape containing platinum group oxides prepared by the method for preparing a hydrogen-sensitive color-changing tape containing platinum group oxides as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Color-changing adhesive tape for hydrogen leakage detection and preparation method of color-changing adhesive tape
CN115505347A
Hydrogen-sensitive functional film for hydrogen leakage detection and preparation method of hydrogen-sensitive functional film
CN117343669A